The Translation Text of Drama “Macbeth”: Grammatical Transformation of Adjunct in Noun Phrase - Firda Zuldi Imamah; Agus Subiyanto (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
Macbeth is one of Shakespeare’s play that used unique and dramatic choice of words in its adjective and noun. Grammatical transformation of adjectival adjunct in noun phrase in the translation text of drama Macbeth has caused the shift of phrase’s meaning. This study aims to identify the grammatical shift by using X-Bar theory. This study is a descriptive qualitative study. The data are collected by using documentation and note taking technique. There are 35 noun phrases collected. The results show that there are 3 types of shift of adjectival adjunct. First, the adjunct is omitted. Second, the adjunct shifts into complementizer phrase. Third, the adjunct shifts into prepositional phrase.